516 Prevalence of carpal tunnel syndrome in patients with transthyretin cardiac amyloidosis. (8th December 2021) - Trimarchi, Giancarlo; Perna, Alessia; Zampieri, Mattia; Argirò, Alessia; Runinski, Robert; Cappelli, Francesco; Di Bella, Gianluca
Abstract: Aims: Carpal tunnel syndrome (CTS) represents an important red flag for transthyretin (ATTR) cardiac amyloidosis (CA). However, no large studies have investigated the prevalence of CTS in wild type ATTR (wtATTR) and hereditary ATTR (hATTR). To investigate the prevalence of CTS in patients with ATTR-CA, both wild type and hereditary, differentiating between monolateral and bilateral carpal tunnel syndrome. Methods and results: 381 patients, 308 male and 73 female, with a definite diagnosis of ATTR CA have been evaluated. Among these, 230 patients with diagnosis of wild-type ATTR (wtATTR) and 151 patients with hereditary ATTR (hATTR) were identified. Patients with diagnosis of hATTR are sorted according to phenotype in cardiologic (43 patients) and mixed when both cardiologic and neurologic phenotype are observed (108 patients). Patients with neurological phenotype without CA were excluded. Overall, CTS is present in 57.6% of ATTR patients; A higher prevalence ( P  < 0.05) of CTS was observed in wtATTR (61.6%) respect to hATTR (51.7%). Monolateral isolated CTS is significantly frequent ( P  < 0.05) in patients with hATTR (35.1%) than in wtATTR (12.7%), on the contrary bilateral CTS is significantly more frequent ( P  < 0.05) in patients with wtATTR (48.5%) than in hATTR (16.6%). Among patients with hATTR, of the 43 patients with cardiologic phenotype, 18 patients (41.9%) have diagnosis of CTS, subdivided in 28% with monolateral CTS and 72% with bilateral CTS. Among hATTR patients with mixed phenotype, 55.6% have diagnosis of CTS, subdivided in 80% with monolateral isolated CTS and 20% with bilateral CTS. Among 151 patients with hATTR, monolateral isolated CTS is significantly more present in patients with mixed phenotype (80% vs. 27%, P  < 0.001) while bilateral CTS is significantly more frequent in patients with cardiologic phenotype (72.2% vs. 20%, P  < 0.001). Conclusions: CTS particularly with bilateral involvement is a common finding in wtATTR patients than in hATTR patients. On the contrary, monolateral isolated CTS is significantly more frequent in patients with hATTR than in wtATTR. Among patients with hATTR, bilateral CTS is significantly more frequent in patients with cardiologic phenotype than mixed phenotype while monolateral isolated CTS is significantly more present in patients with mixed phenotype.